2011
DOI: 10.1103/physreve.84.051128
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of the Beck-Cohen superstatistics

Abstract: Generalized superstatistics, i.e., a "statistics of superstatistics," is proposed. A generalized superstatistical system comprises a set of superstatistical subsystems and represents a generalized hyperensemble. There exists a random control parameter that determines both the density of energy states and the distribution of the intensive parameter for each superstatistical subsystem, thereby forming the third, upper level of dynamics. Generalized superstatistics can be used for nonstationary nonequilibrium sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The q -exponential scaling behavior of interevent times for T < T c can be originated from a simple mechanism, namely a gamma-distributed allocated parameter ( β ) of the local Poisson process, and may be used to explain the interevent time distribution in aftershock sequences. The T c value indicated that in the early aftershock period the majority of interevent times had T values lower than T c and their distributions were described by NESP, while properties such as long-range memory, associated with NESP, became less prominent as the system relaxed and the BG statistical physics recovered [ 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The q -exponential scaling behavior of interevent times for T < T c can be originated from a simple mechanism, namely a gamma-distributed allocated parameter ( β ) of the local Poisson process, and may be used to explain the interevent time distribution in aftershock sequences. The T c value indicated that in the early aftershock period the majority of interevent times had T values lower than T c and their distributions were described by NESP, while properties such as long-range memory, associated with NESP, became less prominent as the system relaxed and the BG statistical physics recovered [ 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The q -exponential behavior of the interevent times can further be viewed in terms of superstatistics, which are based on a superposition of ordinary local equilibrium statistical mechanics with a suitable intensive parameter ( β ) that varies as a gamma distribution on a reasonably wide temporal scale and is supplementary to NESP [ 19 , 23 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The actual value of the signal x may be random variable with the distribution depending on the parameters and, consequently, on the slowly varying averagex. In such superstatistical approach [4,59,1,24,5,64,55,65] the distribution P (x) of the signal x is a superposition of the conditional distribution ϕ(x|x) and the local stationary distribution p(x) of the parameterx,…”
Section: Superstatistical Frameworkmentioning
confidence: 99%